Dual‐Dynamic Modulation of Thermal Radiation and Electromagnetic Interference Shielding with the Self‐Healing Electrochromic Device. Issue 7 (2nd March 2022) - Xu, Gaoping; Wang, Bo; Song, Shanshan; Ren, Zichen; Liu, Dongqi; Zhang, Leipeng; Li, Yao
Abstract: There is a need to develop next generation devices for dual‐dynamic regulation of thermal radiation and electromagnetic interference (EMI) shielding to allow the precise operation of electronic components. Here, a novel, stretchable, and self‐healing electrochromic device with unprecedented dynamic tunability of thermal emittance and electromagnetic interference is developed, which exhibits the thermal emittance modulation (Δε) of 0.37 and 0.43 at 8–14 µm under different voltages and strains, respectively. Additionally, by tuning the strain, the device can achieve the change of EMI shielding efficiency (SE) of 16.1 dB due to the increase of the transmittance for electromagnetic wave between the interleaving of the fibers. Moreover, the device exhibits outstanding mechanical stability (98.7% retention of Δε at 8–14 µm and 97.7% retention of EMI SE after bending for 300 cycles), a remarkable stretching stability (99.2% retention of Δε at 8–14 µm and 98.2% retention of EMI SE after stretching for 50 cycles) and the self‐healing performance (99.8% retention of Δε at 8–14 µm and 99.6% retention of EMI SE after the self‐healing). These results indicate that the device have excellent tunability for EMI shielding and thermal management in communication, military, and smart electronics. Abstract : This study presents the dynamic modulation of electromagnetic interference shielding and thermal radiation based on the highly stretchable and self‐healable device by voltages and strains.